1999
DOI: 10.26719/1999.5.3.565
|View full text |Cite
|
Sign up to set email alerts
|

[Value of immunization data analysis at the district level]

Abstract: This study aimed to demonstrate the importance of analysing local immunization data to improve performance of national prevention programmes. From the immunization registers kept in basic health centres, we identified 1271 children receiving their first vaccine at 3 months. Examination of the age at the subsequent vaccinations and time intervals between vaccinations showed that 81.9% had received all the vaccines required by the Ministry of Health but only 48.5% had received immunization meeting the requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…A total of 4 shortlisted studies observed the effects of vaccine delivery-oriented interventions, which are usually statesponsored and done at a large scale. Out of these studies, one study was a reflex comparison (Bonu, 2003), one study was a retrospective observational study (Goel, 2012), one study was a secondary analysis (Hong, 2005), while one study was a mixed method evaluation study (Sengupta, 2017). The interventions included National Immunization Days (NIDs) (Bonu, 2003), multi-intervention government Immunization campaigns (Goel, 2012; Hong,2005 ), and vaccination outreach programs (Sengupta, 2017).…”
Section: Figure 2 (A): Forest Plot Of Comparison Odds Ratio (95% CI I...mentioning
confidence: 99%
“…A total of 4 shortlisted studies observed the effects of vaccine delivery-oriented interventions, which are usually statesponsored and done at a large scale. Out of these studies, one study was a reflex comparison (Bonu, 2003), one study was a retrospective observational study (Goel, 2012), one study was a secondary analysis (Hong, 2005), while one study was a mixed method evaluation study (Sengupta, 2017). The interventions included National Immunization Days (NIDs) (Bonu, 2003), multi-intervention government Immunization campaigns (Goel, 2012; Hong,2005 ), and vaccination outreach programs (Sengupta, 2017).…”
Section: Figure 2 (A): Forest Plot Of Comparison Odds Ratio (95% CI I...mentioning
confidence: 99%
“…According to the Millennium Development Goal fully immunized children from age twelve months to twenty-three months in year 2001-02 was 53%, which reached to 80% in 2011-12 against the target of 90% fully immunized children. 8 Measles I coverage is also not reaching to the set target. This gap in immunization has led to increase under five mortality rates and infant mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Year 2001-02 reported 57% coverage of measles I in under one year children and has increase to 81% in 2011-12 against target of 90% as mentioned in millennium development goals. 8,9 Financial Situation analysis: In Pakistan, since year 2000, the massive change is seen in the pattern of expenditure on immunization both routine and campaigns to meet the goals. After the 18th amendment the decision-making power for the finance has been change and more power shifted towards the province from the federal ministry.…”
Section: Introductionmentioning
confidence: 99%